STRENGTHENING ELEMENTARY SCHOOL STUDENTS’ RELIGIOUS CHARACTER THROUGH A CONTEXTUAL-BASED ISLAMIC RELIGIOUS EDUCATION MODEL - Aida Rahmi Nasution; Syarfuni Syarfuni; Muhammad Husein; Jumiatun Jumiatun (STAI Ma'had Aly Al-Hikam Malang, 2025)
Religious character is an essential aspect that must be considered in the learning process because strong religious values can serve as a safeguard against anarchic attitudes, moral decline, and various criminal behaviors commonly found in primary education. Therefore, this study focuses on: (1) how a contextual‑based Islamic Religious Education (PAI) learning model is implemented to strengthen the religious character of elementary school students; (2) the strategies used by PAI teachers to develop and reinforce students’ religious character through contextual learning; and (3) the implications of applying the contextual PAI model on strengthening students’ religious character. Islamic Religious Education as a problem‑solving approach cannot be effective if taught merely textually; it needs to be presented contextually. This research employs a qualitative approach with observation, interviews, and documentation as data collection methods, and uses Miles and Huberman’s data analysis techniques, including data grouping, data processing, data verification, and conclusion drawing. The results of the study produced: (1) a contextual‑based PAI learning model for forming students’ religious character; (2) teacher strategies in shaping students’ religious character; and (3) the implications of the contextual PAI model for strengthening students’ religious character.